Optimization of pH Control in Acetic Acid (CH₃COOH)–Sodium Hydroxide (NaOH) Neutralization Process Using a Fuzzy Logic Controller - Arfittariah; Turahyo; Abadi Nugroho; Mey Lista Tauryawati (Universitas Panca Marga, 2026)
Conventional control systems, such as Proportional-Integral-Derivative (PID) controllers, have been widely applied in industrial process control due to their simple structure. However, these systems exhibit significant limitations when dealing with highly nonlinear processes and require retuning whenever plant conditions change. The pH control process represents one of the nonlinear systems in which small variations in hydrogen ion (H⁺) concentration can cause substantial changes in pH values. This study develops an acetic acid (CH₃COOH) and sodium hydroxide (NaOH) titration model as a case study and designs a pH control system based on a Fuzzy Logic Controller (FLC). The proposed FLC system employs two input variables, namely error (with a membership function range of −1 to 1) and error change (Δerror) (with a membership function range of −0.5 to 0.5), along with one output variable representing valve position (with a membership function range of 4–20). Simulations were conducted at three pH set points (4, 7, and 10) to evaluate the dynamic response characteristics of the proposed control system. The simulation results demonstrate that the FLC is capable of achieving a steady-state error below 0.5% for all evaluated set points. Furthermore, the overall simulation error remains below 5%, indicating that the developed titration model provides adequate accuracy. This study confirms that FLC is an effective approach for handling nonlinear characteristics in pH control processes.